Minerals: A Comprehensive Review of Classification, Properties, Formation, and Their Role in Modern Technology and Sustainability - Ramya B; Mahadeva M (International Journal of Crystalline Materials, 2026)
Minerals are naturally occurring, inorganic, solid elements with a definite chemical composition and a characteristic crystal structure. They are the building blocks of rocks. Minerals are the key to the development and progress of human civilization. They are used for the development of infrastructure, electronic gadgets, agriculture, and medicine. This research paper aims to present an exhaustive overview on the field of mineralogy, which includes the definition, classification, physical and chemical properties, geological formation, geographical distribution, industrial uses, and environmental importance of minerals. Additionally, this paper will discuss the current scenario of mineral extraction and the rising need for critical minerals for the development of modern technology. With over 5,700 known mineral species discovered to date, this paper will present a summary on the current knowledge on these topics, which has been developed over decades of geological research. Lastly, this paper will present the future perspectives on mineralogy research, which includes nano mineralogy and the discovery of minerals on other planets.
Keywords: Critical minerals; crystal structure; crystallography; geochemistry; industrial minerals; mineralogy; minerals; ore deposits; rock-forming minerals; silicates